FRAMEWORK ENTREPRENEURIAL SUCCESS FOR YOUNG ENTREPRENEUR - Sidharta, Helena; Ismail, Noor Azizi B.; Suryasaputra, Ruswiati; Rahman, Syed Abidur (Universitas Brawijaya, Indonesia, 2017)
This research is a literature study that aims to find a model to examine factors that play major role in forming a college student as well as business owner to become a successful entrepreneur. Literature study has been done by grouping the individual factors which encourage someone to become entrepreneurs through research that has been done by previous researchers, and then selected factors that effect in the successful journey of an adult entrepreneur. Based on the conducted study it was found that the personality factor is a strong motivation for an individual person who is able to determine someone success. Another interesting factor is the style of parents in educating this individual, in which the authoritative parenting style plays more important role in the success of adult entrepreneurs than other parenting styles. Besides, for an entrepreneur, entrepreneurial competence is needed to support the individual's success. In addition to an entrepreneur, entrepreneurial competence is needed to support the individual's success. Therefore the model generated from this research is the entrepreneurial personality using the big five personality approach so that has five variable manifest and authoritative parenting style as an independent variable to entrepreneurial success, whereas entrepreneurial competence becomes the mediating variable between an independent variable and dependent variable where entrepreneurial competence has six manifest variables.